Hepatitis B vaccination for sex workers: do outreach programmes perform better?. Issue 2 (1st April 2003) - Mak, R; Traen, A; Claeyssens, M; Van Renterghem, L; Leroux-Roels, G; Van Damme, P
Abstract : Objectives: To assess to what extent hepatitis B vaccination of sex workers in Ghent, Belgium, is successful within the context of the existing health services and to compare this with alternative approaches such as outreach programmes; to compare two hepatitis B vaccination schemes in the outreach programme for sex workers. Methods: Testing all first contacts (n = 1096) in the outreach programme for hepatitis B virus (HBV) markers assessed success of hepatitis B vaccination in routine services. The performance of the outreach service was measured by counting the number of sex workers who started hepatitis B vaccination in the programme. The hepatitis B vaccination schemes were assessed by analysing the number of people completing the vaccination. Results: Naturally acquired HBV was found in 11.9% of 1096 sex workers (0.6% HBsAg), and 7% were vaccinated in existing services. In contrast, hepatitis B vaccination using outreach methodology was able to achieve higher vaccination rates: among non-immune sex workers 82.8% received the first dose of vaccine, and 71.5% the second. If given 1 month later, 67.9% received the third dose, in contrast with 47.9%, when given 6 months later. Conclusions: Existing services are not successful in vaccinating sex workers for HBV, in contrast with specifically targeted outreach services. Shorter intervals between vaccine doses gave better compliance.